AN INDONESIAN LEARNERâS READING JOURNAL FOR EXTENSIVE READING - Delfi, Syofia; Yamat, Hamidah (Proceeding 7th International Seminar on Regional Education, 2015)
Abstract Reading Journal is a possible instrument to find out what and how learners do extensive reading and explore their perceptions about what and how they read. This article is based on one of instruments for a study on Exploring Extensive Reading in Developing English Language Competency of Indonesia EFL Learners. The study is a case study and one of the data collected through journal entry. This article aims to present the findings of the study in terms of types of reading materials that an Indonesian learner read for extensive reading and learnerâs perceptions about the reading materials. The findings from this instrument are: (1) types of reading materials that an Indonesian learner read for extensive reading were a book about health and a novel about ditective and (2) an Indonesian learnerâs perceptionsâ about reading materials were her interest in terms of the use for the book and pleasure for the novel. This study suggests that learners need to write journal for extensive reading materials. This study also recommends to include what learners learn in journal entry by reading the novel selected for further.Keywords: characteristics and benefit of Extensive Reading